2020
DOI: 10.1177/0733464820929863
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Perspectives on Fall Risk: Linking Results to the ICF

Abstract: The aim of this study is to establish the perceptions of older adults in the South African context regarding falls and to link these perceptions to the International Classification of Functioning, Disability and Health (ICF). Data were analyzed by a summative, conventional, and deductive approach. The analysis indicated that the Body Function and Structure codes were most frequently used during the discussions, but the contextual analysis of the most frequently used categories indicated that Activities and Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Outcomes linked to the body structures domain appear to be of greater importance to clinical experts than healthcare consumers. This is in agreement with research describing outcomes of significance for falls risk assessment in older adults, where body structure outcomes made up 6% of significant outcomes for consumers [13] compared to 18% for healthcare practitioners [36].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Outcomes linked to the body structures domain appear to be of greater importance to clinical experts than healthcare consumers. This is in agreement with research describing outcomes of significance for falls risk assessment in older adults, where body structure outcomes made up 6% of significant outcomes for consumers [13] compared to 18% for healthcare practitioners [36].…”
Section: Discussionsupporting
confidence: 90%
“…Each level expands on specific details, for example, within the activity and participation domain, there is a level one chapter for mobility, a second level for walking and moving, a third level for walking, and a fourth level for walking short distances. The ICF framework is used globally for outcome evaluation in the clinical rehabilitation setting [12], and it is used in research to classify and assess outcome measures used in patient assessment [13,14]. In lung cancer, no studies have applied the ICF to comprehensively examine which outcomes are important to patients and their caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…Confidence in one's own physical abilities might be an important variable in fostering gait speed and consequently enabling an independent lifestyle. Previous findings suggest that activities and participation could also facilitate a decreased fall risk (de Clercq et al, 2020). Studies often examine QoL among older adults without explicitly defining this construct.…”
Section: Discussionmentioning
confidence: 99%
“…The ICF is an internationally recognised framework that is underpinned by the biopsychosocial model of disability (Dantas et al, 2020 ). This comprehensive framework provides a scientific basis and common language for healthcare professionals worldwide to describe and classify falls, their associated risk factors in older adults (De Clercq et al, 2021 ), causes of falls and interventions aimed at fall prevention (Baris & Seren Intepeler, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the activity domain, balance and falls gait (including stairs) and transfers are measured, while in the participation domain, it focuses on community function, home management, leisure and recreational activities role function and shopping (Academy of Neurologic Physical Therapy, 2013 ). This is important, as a recent study has found that fall assessment should focus on the activities and participation domains as this may decrease the risk of falling in older adults (De Clercq et al, 2021 ). These findings are supported by Johnson ( 2018 ) who explains that ‘increased knowledge of the activities that are linked to falls and common fall-related injuries could be a valuable contribution to the prevention of falls in community-dwelling older adults’ (p. 22).…”
Section: Introductionmentioning
confidence: 99%